Human safety and shark conservation: an analysis of surfer risk perceptions and attitudes towards shark management - Sheridan, Katherine (Department of Biological Sciences, 2021)
South Africa has a history of human conflict with sharks and shark safety management. Management of this conflict differs throughout the country, with Cape Town opting for a non-lethal approach in the form of the Shark Spotters programme, and Kwa-Zulu Natal (KZN) opting for a lethal approach using shark nets and drumlines. Lethal management of sharks stems from a belief that without it, people would be too afraid to go in the water, leading to adverse effects on tourism and other associated industries. I assessed surfers' perceptions of risk from sharks, how they value sharks, their knowledge of sharks, and their attitudes towards shark management. I surveyed surfers at Muizenberg Beach in Cape Town, and North Beach and Bay of Plenty Beach in Durban by asking them to answer questions in a questionnaire. A conjoint analysis assessed how likely respondents were to go in the water under various scenarios using situational factor levels related to shark presence, surf/sea and spotting conditions, and whether other people were in the water. The questionnaire results showed no support for lethal shark control and only 8.3% of respondents were aware the nets used in KZN were a lethal form of shark control. Respondents had good knowledge of shark ecology and a positive perception of sharks, both of which have been shown to benefit shark conservation in previous studies. A multiple linear regression model showed a positive correlation between perception of shark risk and perception of other risks, such as car accidents and natural disasters, with respondents perceiving other risks as greater than shark risks. In the conjoint analysis, shark presence was the most influential factor for surfers deciding to go in the water, but respondents were more likely to go in under good surf conditions and spotting/sea conditions even if a shark had been seen recently. Overall, sharks do not deter people from going in the ocean. Implications of these results undermine the longstanding argument that lethal shark management is necessary to protect tourism. Furthermore, the lack of knowledge that lethal shark control is being practised in South Africa coupled with the opposition to lethal management found in this study highlights a clear disconnect between water users and shark managers in KZN.